2012
DOI: 10.1073/pnas.1120265109
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus binds its host cell using multiple dynamic interactions

Abstract: Influenza virus belongs to a wide range of enveloped viruses. The major spike protein hemagglutinin binds sialic acid residues of glycoproteins and glycolipids with dissociation constants in the millimolar range [Sauter NK, et al. (1992) Biochemistry 31:9609-9621], indicating a multivalent binding mode. Here, we characterized the attachment of influenza virus to host cell receptors using three independent approaches. Optical tweezers and atomic force microscopy-based single-molecule force spectroscopy revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 35 publications
11
106
0
1
Order By: Relevance
“…The dissociation coefficient (Kd) between HA and its receptor is 1.4–6.5 × 10 −3 M1112, which is 1 × 10 5 –10 11 -fold greater than the Kd of adhesive proteins on other viruses (e.g., the E2 protein of SFV and the G protein of VSV) or the Kd of several physiological ligands (Supplementary Table S1)131415161718. Moreover, the HA-receptor binding half-life is 0.8–5.5 s19, whereas the half-life of influenza virus internalisation is 10–15 min20. Therefore, stable association of IAV with the cell surface requires multiple HA-receptor binding events.…”
mentioning
confidence: 94%
“…The dissociation coefficient (Kd) between HA and its receptor is 1.4–6.5 × 10 −3 M1112, which is 1 × 10 5 –10 11 -fold greater than the Kd of adhesive proteins on other viruses (e.g., the E2 protein of SFV and the G protein of VSV) or the Kd of several physiological ligands (Supplementary Table S1)131415161718. Moreover, the HA-receptor binding half-life is 0.8–5.5 s19, whereas the half-life of influenza virus internalisation is 10–15 min20. Therefore, stable association of IAV with the cell surface requires multiple HA-receptor binding events.…”
mentioning
confidence: 94%
“…Recently Sieben et al . [30] determined the force of the interaction between HA and sialic acid on the cell membrane using optical tweezers and an HA-coated bead. By contrast, we developed a novel method, using optical tweezers to trap heterogeneous virus particles.…”
Section: Discussionmentioning
confidence: 99%
“…All-atom MD simulations have been applied to numerous crystal complexes of HAs with receptor analogues to characterize binding mode dynamics, as well as to study recognition and specificity based on bound receptor conformations and interaction profiles [8, 9, 10, 11, 12]. Recent modeling and simulation work has also revealed that HA receptor specificity may depend on extended glycan structure and the ability to accommodate bidentate binding to biantennary glycans [13, 14].…”
Section: Envelope Proteinsmentioning
confidence: 99%